Dynamic Infant-Parent Affect Coupling during the Face-to-Face and Still-Face Paradigm: Inter- and Intra-Dyad Differences - Chow, Sy-Miin (2010)
We examined dynamic infant-parent affect coupling using the Face-to-Face/Still-Face (FFSF) paradigm. The sample included 20 infants whose older siblings had been diagnosed with Autism Spectrum Disorders (ASD-sibs), and 18 infants with comparison siblings (COMP-sibs). A series of extended autoregressive models was used to represent the self-regulation and interactive dynamics of infants and parents during FFSF. Significant bidirectional affective coupling was found between infants and parents, with the former serving as the “leading members” of the dyads. Further analysis of within-dyad dynamics revealed ongoing changes in concurrent infant-parent linkages both within and across different FFSF episodes. The importance of considering both inter- and intra-dyad differences is discussed.